1996
DOI: 10.1097/00002508-199609000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Abuse and Chronic Musculoskeletal Pain: Prevalence and Psychological Factors

Abstract: These data extend the relationship between sexual abuse and pain to a Swedish population suffering from musculoskeletal complaints. Our findings suggest that intervention in the pain treatment setting may need to address further the problems of effective coping strategies and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…Abused patients were found to report higher AD and lower LC on the MPI. These results are consistent with findings by Linton et al 23 and Spertus et al, 49 who found higher psychological distress, in terms of MPI AD and LC in abused pain patients. These authors concluded that exposures to traumatic events may alter patients' ability to manage their emotional responses to stressful circumstances, such as the stress of chronic pain.…”
Section: Discussionsupporting
confidence: 93%
“…Abused patients were found to report higher AD and lower LC on the MPI. These results are consistent with findings by Linton et al 23 and Spertus et al, 49 who found higher psychological distress, in terms of MPI AD and LC in abused pain patients. These authors concluded that exposures to traumatic events may alter patients' ability to manage their emotional responses to stressful circumstances, such as the stress of chronic pain.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, women who reported penetrative sexual abuse exhibited significantly more psychological distress than non‐abused women. These results are consistent with those derived from studies among chronic pain patients showing that sexually abused women presented higher levels of psychological distress compared with non‐abused women [21,23–26,44,47,48]. Our study design did not allow us to evaluate how much of the distress is independently explained by the presence of pain, sexual abuse history, or their combined effect.…”
Section: Discussionsupporting
confidence: 84%
“…2009). Sexually abused women with chronic musculoskeletal pain were found to have poorer scores than non‐abused ones on 27 of 29 variables (Linton et al . 1996, Linton 2002).…”
Section: Resultsmentioning
confidence: 99%